Autoantibodies Against C3b—Functional Consequences and Disease Relevance - Vasilev, Vasil V.; Radanova, Maria; Lazarov, Valentin J.; Dragon-Durey, Marie-Agnes; Fremeaux-Bacchi, Veronique; Roumenina, Lubka T. (Frontiers in Immunology, 2019)
The complement component C3 is at the heart of the complement cascade. It is a complex protein, which generates different functional activated fragments (C3a, C3b, iC3b, C3c, C3d). C3b is a constituent of the alternative pathway C3 convertase (C3bBb), binds multiple regulators, and receptors, affecting thus the functioning of the immune system. The activated forms of C3 are a target for autoantibodies. This review focuses on the discovery, disease relevance, and functional consequences of the anti-C3b autoantibodies. They were discovered about 70 years ago and named immunoconglutinins. They were found after infections and considered convalescent factors. At the end of the twentieth century IgG against C3b were found in systemic lupus erythematosus and recently in lupus nephritis, correlating with the disease severity and flare. Cases of C3 glomerulopathy and immune complex glomerulonephritis were also reported. These antibodies recognize epitopes, shared between C3(H2O)/C3b/iC3b/C3c and have overt functional activity. They correlate with low plasmatic C3 levels in patients. In vitro, they increase the activity of the alternative pathway C3 convertase, without being C3 nephritic factors. They perturb the binding of the negative regulators Complement Receptor 1 and Factor H. The clear functional consequences and association with disease severity warrant further studies to establish the link between the anti-C3b autoantibodies and tissue injury. Comparative studies with such antibodies, found in patients with infections, may help to uncover their origin and epitopes specificity. Patients with complement overactivation due to presence of anti-C3b antibodies may benefit from therapeutic targeting of C3.